Attentive Groupware Systems: A Framework and a Prototype Tool - Ferreira, António (2007)
We address the development of software devices that can be installed on groupware systems to help people stay attentive and be more productive during computer-mediated collaboration. We introduce a framework that derives attentive devices from groupware mediation modes to take into account attentional phenomena, and demonstrate the framework's role in an attentive electronic brainstorming tool. Finally, we describe a laboratory experiment to evaluate the impact on group performance caused by the use of the attentive devices, and present preliminary results that encourage further evaluation on the 'opportunity seeker', which minimises interruptions while the user is typing an idea